Review of Photovoltaic Cells for Solar-Powered Aircraft Applications - Bashir Danjuma, Safyanu; Omar, Zamri; Noor Abdullah, Mohd (International Journal of Engineering and Technology, 2018)
This review paper presents the study of photovoltaic cells for solar-powered aircraft applications. Different PV cells and Maximum Power Point Tracker (MPPTs) are evaluated, and those applicable to solar-powered aircraft are stated. A good irradiance model is developed based on Malaysia as a case study using R.SUN (IET, 2013). The model was developed using the Photovoltaic Geography Information System (PVGIS) of the European Union. PVGIS provide online interactive maps of potentials in Europe, Asia and Africa. The deviation from the tilt angle and geographical location of the flight to follow the cambered airfoil, the camber efficiency is introduced. The cells are designed to dispose of the wings and connected in series to ensure they have a similar orientation. For the flexibility of PV silicon cells for encapsulation on the wing, thin film solar cells is ascertaining suitable to be the best. For the silicon solar cell, because of their brittle nature, two methods were adopted to ensure the silicon solar cell is bend to the airfoil to minimise loss of efficiency.Â Â